Specific Features Of Reading And Its Role In Teaching A Foreign Language - Muxabbat Ikromovna Tursunova (Indonesian Journal of Innovation Studies, 2022)
this article deals with the identifying the most effective methods and means of teaching reading in foreign language lessons. In addition, author provides the techniques and means of teaching reading and identifies those that contribute to the formation of interest in reading in a foreign language.